Cytogenetic, molecular, and morphological characterization of Odocoileus pandora (Merriam, 1901) (Artiodactyla, Cervidae) - Sandoval, Eluzai Dinai Pinto [UNESP]; Bernegossi, Agda Maria [UNESP]; Gallina, Sonia; Reyna-Hurtado, Rafael; Duarte, José Maurício Barbanti [UNESP] (Canadian Science Publishing, 2023)
The Yucatan brown brocket deer was initially described as Mazama pandora Merriam, 1901. Phylogenetic analysis of mitochondrial DNA recovered the species as sister group of the genus Odocoileus and subsequently the species was repositioned to this genus naming Odocoileus pandora (Merriam, 1901). However, there is still a lack of taxonomic consensus that could assist in nomenclature definition of the species. We aim to clarify the taxonomy of O. pandora through an integrative assessment using morphological, cytogenetic, and molecular data from recently collected specimens. Morphological characterizations identified O. pandora as a medium-sized brocket deer. The skull shows an inflated auditory bulla and a narrow zygomatic arch. Males present long, broad, spike-like antlers converging inward, marked with deep longitudinal grooves. Odocoileus pandora shows a karyotype with 2n = 60 FN = 74. Bacterial artificial chromosome clone hybridization showed that centric and tandem fusions, and inversions are involved in karyotypical divergences between O. pandora, S. gouazoubira, M. americana,andO. virginianus.Our phylogeny based on Bayesian Inference of mitogenome recovered O. pandora as monophyletic within the subtribe Odocoileina, with Odocoileus as sister taxa. Morphological and genetic characteristics of O. pandora agrees in differencing the Yucatan brown brocket from Mazama and Odocoileus genera. Therefore, a new generic name should be indicated for this taxon.
Keywords: cervid; cytotaxonomy; mitochondrial phylogeny; morphology; Odocoileus pandora; Yucatan brocket deer